The risk for falls in older people in the context of objective functional studies - Ignasiak, Zofia; Skrzek, Anna; Kozieł, Sławomir; Sławińska, Teresa; Posłuszny, Paweł; Rożek, Krystyna (Anthropological Review, 2015)
Falls may occur in each ontogenesis phase, but they become more frequent in the elderly and lead to serious health consequences. Dynamic changes in senior citizens’ environment and lifestyle makes studies of risk for falls necessary. To determine the relationship between the risk for falls and the objective functional and structural examination in the elderly living in Poland. The research consisted of 196 females and 61 males aged 60–88 recruited from health clinics, senior citizen centers and Universities of the Third Age between 2009–2012. Following parameters were collected: functional physical tests “30 second Chair Stand Test” and Timed Up and Go Test”, the flexor muscles and knee extensors force, the bone mineral density was measured in distal radius of the forearm with the EXA – 3000, the total risk for fall assessed by 5 tests by abbreviated version of Fallscreen test. Multiple linear regression and linear correlation were used for assessment of relationship with total estimated risk for fall and other parameters. The subjects displayed significant dimorphic differences within the range of the functional parameters and bone mineral density to the advantage of males. Only in women results revealed a significant link between the risk for falls and the dynamic balance, as well as the maximum quadricep muscle force equal. Strength of the lower limb muscles seems to be critical for decreasing the risk for fall. Special programs for strengthening this part of the body for older people should be elaborate.